2006
DOI: 10.1177/1934578x0600100112
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of Crocetin and Crocin (Digentiobiosyl Ester of Crocetin) from Saffron

Abstract: Functional plant foods and medicinal herbs provide a wide variety of natural products for new drug research and development. Crocetin and crocin (digentiobiosyl ester of crocetin) are the major bioactive ingredients of saffron which is used as a costly spice, food colorant and traditional herbal medicine. These particular carotenoids have gained much research attention for their extensive pharmacological activities. Following oral administration, crocetin is rapidly absorbed into the blood circulation and wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 56 publications
0
14
0
2
Order By: Relevance
“…The dried, red stigmas of Crocus sativus L. (saffron) are a very expensive spice known as saffron, which is used as a food flavoring, a coloring agent and as a traditional herbal medicine (Xi & Qian, 2006). The postharvest dehydration process is necessary to convert C. sativus stigma into the saffron spice.…”
Section: Introductionmentioning
confidence: 99%
“…The dried, red stigmas of Crocus sativus L. (saffron) are a very expensive spice known as saffron, which is used as a food flavoring, a coloring agent and as a traditional herbal medicine (Xi & Qian, 2006). The postharvest dehydration process is necessary to convert C. sativus stigma into the saffron spice.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been used in Tibet as a tonic for the cardiovascular and nervous system. Modern studies showed that 4 , along with its derivatives could be useful in the treatment of various diseases such as cancer, coronary heart diseases and hypertension (Xi & Qian, 2006 ). As mentioned earlier, various investigations demonstrated the effectiveness of 4 in increasing oxygen diffusivity and oxygen consumption by the body tissues (Xi & Qian, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, saffron is the most expensive spice in the world. The copious amount of water needed, coupled with a difficult irrigation process for saffron cultivation are the key reasons for its abysmally higher cost (Xi & Qian, 2006 ). Today, 1 kg of saffron costs ~US $200 (estimate).…”
Section: Introductionmentioning
confidence: 99%
“…This has been demonstrated in vivo and in vitro [ 61 , 72 , 73 ]. Notably, crocetins are more readily absorbed than crocins in the gastrointestinal tract of animals [ 74 ]. Additionally, crocins are metabolized to crocetins when administered orally [ 74 , 75 , 76 ].…”
Section: Saffron: Reported Biologically Active Compounds and Their Ph...mentioning
confidence: 99%
“…Notably, crocetins are more readily absorbed than crocins in the gastrointestinal tract of animals [ 74 ]. Additionally, crocins are metabolized to crocetins when administered orally [ 74 , 75 , 76 ]. However, it has not yet been elucidated how readily crocin is metabolized in humans.…”
Section: Saffron: Reported Biologically Active Compounds and Their Ph...mentioning
confidence: 99%